DESAIN FLEKSIBEL VIBRANT DALAM PERANCANGAN INTERIOR KANTOR KONTEN KREATOR (Jurnal iSpectrum, 2023)
The development and use of social media has become a part of human life today. This affects human activity in various aspects including health, economy, welfare, and self-development. Social media can attract users' attention by developing materials and creating content or content that can provide information, entertain or influence society. The need for increased content increases the importance of the role of a content creator. In addition, there is a social media specialist profession that supports the development of content. In creating content, a supportive work environment is needed, with technology that can accommodate all needs in content creation, but in Bali itself there are still not many facilities that meet these needs. Therefore, it is necessary to design the interior of the content creator office which aims to provide a place for content creators and social media specialists to work, equipped with studio space and other supporting facilities. With an industrial theme and flexible vibrant concep,  it is hoped that this design will provide adequate facilities for content creators and social media specialists in Bali.